Sistem Informasi Praktik Kerja Lapangan (SIPRAKLAP) Pada SMK Berbasis Web Menggunakan Metode Waterfall - Taufik, Andi (Universitas Multi Data Palembang, 2024)
Field Work Practice is a form of activity to achieve the mission of Vocational High Schools (SMK) that produce graduates to be absorbed in the world of work. With the increasing acceptance of students every year, more and more students have to do PKL activities. However, when carrying out the PKL registration process, the lack of information about PKL received by students so that they do not get a quota for PKL places, the management of PKL activity data is still carried out manually by the hubin so that the hubin requires time in checking the status of students who have not, are and have done PKL, assessment of street vendors and print certificates To overcome these problems, a web-based Field Work Practice Information System (SIPRAKLAP) was created, which makes it easy to find PKL information, PKL reports, assessments and print PKL certificates. The System Development Model used in this study uses a waterfall model, starting from the System Needs Analysis Stage, System Design, Application of Coding, Testing, and Support. And it uses MySQL database and PHP programming language.